1999
DOI: 10.1007/s001470050178
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term results of ATG induction therapy for delayed graft function compared to conventional therapy for immediate graft function

Abstract: The use of polyclonal antibodies for delayed graft function (DGF) was tested in 83 renal allograft recipients. Conventional immunosuppression (CI) was given to 52 patients with immediate graft function (IGF) while 31 patients with DGF received the polyclonal antibody ATG. Administration of OKT3 was restricted to steroid-resistant acute rejections in both groups. The incidence and severity of acute rejections, graft survival rate, CMV infections, and lymphocyte subsets were examined. ATG patients experienced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Because of cost issues, side effects, and excessive immunosuppression, the use of ALA is restricted to treatment of steroid‐resistant rejection, vascular rejection, and to prevent rejection in patients at high immunological risk (17–22). T lymphocyte activation and lysis, with release of cytokines, are responsible for CMV activation from latency (9, 20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Because of cost issues, side effects, and excessive immunosuppression, the use of ALA is restricted to treatment of steroid‐resistant rejection, vascular rejection, and to prevent rejection in patients at high immunological risk (17–22). T lymphocyte activation and lysis, with release of cytokines, are responsible for CMV activation from latency (9, 20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…to CD8 T cells decreased following treatment with anti-thymocyte globulin, which was attributed to a decrease in the number of CD4 + cells and expansion of the CD8 + peripheral T cells, and Bas et al found that acquisition of donor unresponsiveness was correlated with increased numbers of CD8 + CD45RA + T cells in the peripheral blood (49,50). An antigen-nonspecific CD8 + suppressor population has also been described that inhibits T cell proliferation and CTL function (51).…”
Section: Figure 10mentioning
confidence: 99%
“…Although most grafts with delayed function recover spontaneously (1), DGF remains a significant risk factor for acute rejection and graft loss (2)(3)(4). The benefits of delaying cyclosporine (CsA) introduction in order to reduce risk of DGF have not been clearly established in de novo renal transplant patients (5)(6)(7)(8). In renal transplant recipients who experience DGF, CsA has been reported to decrease graft survival, prolong the time to recovery of graft function and extend the duration of hospitalization (9,10).…”
Section: Introductionmentioning
confidence: 99%